2006
DOI: 10.1016/j.aca.2005.12.029
|View full text |Cite
|
Sign up to set email alerts
|

C6-alcohols as varietal markers for assessment of wine origin

Abstract: A significant part of the compounds present in wines having six carbon atoms, the C 6 -compounds, derive from grape polyunsaturated fatty acids (primarily originated from membrane lipids), namely linoleic and ␣-linolenic acids, through a cascade of enzymatic reactions. This biochemical pathway yield C 6 -aldehydes, which are subsequently reduced to C 6 -alcohols, which can, in turn, be esterified to produce esters. As the C 6compounds derive from varietal precursors, they could hypothetically contribute to jud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 24 publications
4
135
1
1
Order By: Relevance
“…However, many studies report stable alcohol concentrations during the ageing of wines (Marais, 1978;Roussis et al, 2005;2007;Blake et al, 2009). Unlike other higher alcohols, the concentration of hexanol can increase during storage, which is probably due to the oxidation of linoleic and linolenic acids (Oliveira et al, 2006).…”
Section: Sauvignon Blanc Ageing and Oxidationmentioning
confidence: 99%
“…However, many studies report stable alcohol concentrations during the ageing of wines (Marais, 1978;Roussis et al, 2005;2007;Blake et al, 2009). Unlike other higher alcohols, the concentration of hexanol can increase during storage, which is probably due to the oxidation of linoleic and linolenic acids (Oliveira et al, 2006).…”
Section: Sauvignon Blanc Ageing and Oxidationmentioning
confidence: 99%
“…MNbw natural Grillo base wine; MCbw-1 conventional Grillo base wine 1; MCbw-2 conventional Grillo base wine 2. * significant differences among attributes of the wines fermentative phase (pressing and maceration) (Oliveira et al 2003) and might positively affect the organoleptic complexity of wines. As detected in other spontaneously fermented wines, high level of esters, mainly acetate ester, were also observed in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…Wine volatile compounds were analysed by GC-MS according to the method proposed by Oliveira et al (2006).…”
Section: Extraction and Chromatographic Analysis Of Wine Volatilesmentioning
confidence: 99%
“…Rapp et al (1993) showed that the contents of E-3-hexenol and its isomer Z-3-hexenol are the most important analytical parameters to discriminate monovarietal wines of Riesling, Müller-Thurgau, Kerner, Scheurebe, Ehrenfelser and Bacchus. Oliveira et al (2006) concluded that the E-3-hexenol/Z-3-hexenol ratio could discriminate Loureiro clearly from Alvarinho wines from Northern Portugal.…”
Section: -Compoundsmentioning
confidence: 99%